2020
DOI: 10.1007/s00270-020-02642-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Trans-Arterial Radioembolization in Hepatic Malignancies in Europe: First Results from the Prospective Multicentre Observational Study CIRSE Registry for SIR-Spheres Therapy (CIRT)

Abstract: Purpose To address the lack of prospective data on the real-life clinical application of trans-arterial radioembolization (TARE) in Europe, the Cardiovascular and Interventional Radiological Society of Europe (CIRSE) initiated the prospective observational study CIRSE Registry for SIR-Spheres® Therapy (CIRT). Materials and Methods Patients were enrolled from 1 January 2015 till 31 December 2017. Eligible patients were adult patients treated with TARE with Y90 resin microspheres for primary or metastatic live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 69 publications
(89 reference statements)
9
54
1
Order By: Relevance
“…It might have an impact on the response tumor and survival. However, our study reports real-life experience with Y90 TARE in a tertiary academic French center, and results are in accordance with those of previous registries [ 36 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It might have an impact on the response tumor and survival. However, our study reports real-life experience with Y90 TARE in a tertiary academic French center, and results are in accordance with those of previous registries [ 36 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several ongoing prospective studies have produced encouraging intermediate results and may confirm the role for TARE in the therapeutic arsenal for CCA [ 34 , 35 ]. Indeed, the first results from the CIRSE registry in Europe using SIR-Spheres therapy recently reported and analyzed 1027 patients in real-life conditions [ 36 ]. Overall, 68.2% of the intention of treatment was palliative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our series included 13.9% inoperable iCC patients treated with SIRT in 2020. Multiple retrospective and prospective series reported good tolerability and objective response rates, with 12–14 months median OS [ 31 , 32 ], comparable to the data reported after TACE [ 33 ]. The role of SIRT in iCC is yet not well-defined [ 7 ].…”
Section: Discussionsupporting
confidence: 53%
“…Results of randomised trials for SIRT (SIRCCA randomised phase II trial, clinicaltrials.gov identifier NCT02807181) and for EBRT (ABC-07 randomised phase II trial, ISRCTN identifier 10639376) are awaited, but the early closure of SIRCCA might lead to insufficient power. Interestingly, different publications reported secondary resection following downsizing with IAT of initially unresectable iCC, evaluated in the pooled analysis as 14.6% of patients treated with systemic chemotherapy in the first-line setting [14][15][16][17][18][19][20], with a potential for long-term survival for these patients [21]. Analysis of landmark survival of patients with BTC treated with systemic chemotherapy suggested that patients treated with combination therapy, for iCC and with locallyadvanced disease had higher probability of further survival [22].…”
Section: Discussionmentioning
confidence: 99%